A Web-Based Teacher Performance Behavior Evaluation Using BARS Method - Farhan Pratama; Yus Sholva; Fauzan Asrin (Universitas Pancasakti, 2026)
The assessment of teachers’ professional performance behavior plays a crucial role in improving the quality if educatuin. However, at Sekolah Dasar Negeri 01 Sungai Raya Kepulauan, the assessment system still relies on MS Excel and conventional document filing, leading to limitations in transparency, efficiency, and accuracy. Teachers and school principals face difficulties in managing assessment data, making the process suboptimal. To address this issue, a web-based assessment system was developed using the Behaviorally Anchored Rating Scale (BARS) method, which aligns with ASN BerAKHLAK values. This system allows for flexible teacher performance behavior assessments via electronic devices such as smartphones and computers. The system development method employed is the Systems Development Life Cycle (SDLC) with the Rapid Application Development (RAD) model. The system is implemented using PHP as the programming language, MySQL as the database, and designed with Unified Modeling Language (UML). Black Box tesing result indicated that the system successfully meets user needs and enhaces the efficiency and transparency of teacher performance behavior assessments in accordance with ASN BerAKHLAK values.